The cleansing effect of minimum wages - Minimum wages, firm dynamics and aggregate productivity in China - Sandra Poncet; Florian Mayneris; Tao Zhang (Fondation pour les études et recherches sur le développement international (FERDI), 2014)
We here consider how Chinese firms adjust to higher minimum wages and how these affect aggregate productivity, exploiting the 2004 minimum-wage reform in China. We find that higher city-level minimum wages reduced the survival probability of firms which were the most exposed to the reform. For the surviving firms, thanks to signicant productivity gains, wage costs rose without any negative employment effect. At the city-level, our results show that higher minimum wages affected aggregate productivity growth via both productivity growth in incumbent firms and the net entry of more productive firms. Hence, in a fast-growing economy like China, there is a cleansing effect of labor-market standards.
Keywords: F10; F14; O14; 330